Comparative study on quality characteristics of pickled and fermented sturgeon (Acipenser sinensis) meat in retort cooking. (3rd April 2019) - Zhu, Lulu; Yang, Fang; Gao, Pei; Yu, Dawei; Yu, Peipei; Jiang, Qixing; Xu, Yanshun; Xia, Wenshui
Summary: Sturgeon ( Acipenser sinensis ) meat has not been fully utilised due to quality defects which were raised by Chinese sturgeon processing industry. This study was aimed to develop a high‐quality sturgeon meat product and the effect of fermentation on qualities was studied. Results showed that fermentation with Saccharomyces cerevisiae could enhance 'mushroom', 'fruity' and 'chocolate' flavour by 1‐octen‐3‐ol, ethyl acetate and 3‐methyl‐butanal; and enrich flavour through mild lipid oxidation and hydrolysis. In addition, fermentation could give an attractive colour with higher a *, b * and L * value. Texture properties were also improved with higher hardness, springiness, gumminess and chewiness. Higher free amino acids, TCA‐soluble peptides and taste score in fermented sturgeon meat indicated better flavour and taste. The organoleptic evaluation suggested an overall satisfactory of wine‐aroma sturgeon meat by fermentation with S. cerevisiae . Abstract : Sturgeon meat could obtain pleasant wine‐aroma flavour by yeast fermentation. Flavour of fish was improved with alcohol and ester compounds; and mild lipid oxidation. Texture, colour and taste of sturgeon meat were improved by fermentation with yeast.